Pengaruh Penggunaan Artificial Intelligence terhadap Kemampuan Problem Solving Mahasiswa Generasi Z melalui Kemandirian Belajar dalam Menyelesaikan Tugas Akademik - Agustinus Tantiono (LPPM Universitas Widya Dharma Pontianak, 2026)
Abstract The growing adoption of digital technologies, especially Artificial Intelligence (AI), has transformed the ways in which students engage in learning and acquire knowledge. The ease of searching for information, completing assignments, and assisting with academic problem-solving can lead to excessive use of AI, fostering dependency and reducing students' independent thinking skills. This study aims to analyze the effect of AI use on students' problem-solving abilities through independent learning as a mediating variable. This study employed a quantitative survey method was used in the research process, distributing questionnaires to students as respondents. Data analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of the SmartPLS application. The results are expected to show whether AI use positively or negatively affects students' problem-solving abilities directly, and to what extent independent learning mediates this effect. This study also aims to highlight the importance of using AI wisely as a learning tool, rather than relying on it for completing coursework. Keywords: Artificial Intelligence, problem-solving, independent learning, students, SmartPLS.